Dimensionamento empírico de realce em Sublevel Stoping - Michel Melo Oliveira (2012)
Empirical methods should be applied only in situations where the features are similar to those used in their original database. The Stability Graph methodologies proposed by Mathews et al. (1981) and by Potvin (1988) are used to design open stopes. Case studies of Canadian and Australian mines bear the two propositions. There is no evidence that these methodologies can be extrapolate to the geomechanical features of Brazilian mines. The main objective of this study was to find evidence supporting the use of these approaches for geomechanical Brazilian conditions. This study consisted of collecting data from Brazilian mining companies that employs sublevel stoping mining method, estimate the operational dilution, as well as the hydraulic radius and the Stability Number for each stope face. Numerical modeling was used to obtain the stability number factor related to the stresses around the excavation. The Stability Graph Methodologies proposed by Mathews et.al (1981), Potvin (1988) and Mawdesley et al. (2001) have been used to compared the results with the limits of stability defined by each author. The analysis of 65 surfaces (hangingwall, footwall, stope end, stope begin and back) of 17 stopes were used in this study. Usually the hangingwalls and the backs are more unstable and, therefore, were analyzed with greater concern. The parameters needed for this analisys may present a bias depending on the stope face observed. All walls were analyzes but hanginwalls and backs, were reviewed with greater emphasis. The restricted database does not allow to conclude that the Brazilian mines are in agreement with the methodologies evaluated, and does not support the use of different stability limits. A larger number of case studies should be used to validate the efficacy of these methods in Brazilian mines.